Model-model pengembangan kebijakan pendidikan - Aini, Qurratul Aini; Ema Rizky Ananda (JURNAL PENDIDIKAN DAN SAINS, 2023)
Education is very important in human intelligence. This article aims to describe models of educational policy development. This research uses qualitative research with a literature study approach. The results of this research show that the education policy model consists of three things, namely: (1). Construction model, (2). Analysis model, and (3). Implementation model. Construction models include institutional models, system models, mixed survey models, process models, classical theoretical models, rational models, incremental models, strategic models, democratic models and group models, game models, and deliberative models